SVPWM Technique for Decentralized Controlled Three-Phase, Multi-Level Power Converters - Nguyễn Phú Công; Phan Quốc Dũng; Nguyễn Đình Tuyên (Journal of Technical Education Science, 2025)
This paper presents the implementation of space vector pulse width modulation (SVPWM) for local controllers in a decentralized modular multilevel power converter (MMC) structure. The modules are established to communicate with four neighboring modules, two modules in columns and two modules in a phase. The switching vectors and switching times are automatically determined by the modules based on the information received by the modules during the communication process. The proposed structure and method enable the decentralized power converters to automatically adjust the dynamic structure when some modules fail or according to the criteria of optimizing operating conditions. The communication settings and implementation of SVPWM can be viewed as a multilevel modulation method. Each local controller is responsible for calculating the pulse width modulation (PWM) signals for each individual module, the number of calculations required in a PWM cycle is much lower when compared to the power converter using a centralized controller. A model of the decentralized control power converter is built on Matlab/Simulink software to evaluate the proposals.